Evidence for non‐methanogenic metabolisms in globally distributed archaeal clades basal to the Methanomassiliicoccales. (27th November 2020) - Zinke, Laura A.; Evans, Paul N.; Santos‐Medellín, Christian; Schroeder, Alena L.; Parks, Donovan H.; Varner, Ruth K.; Rich, Virginia I.; Tyson, Gene W.; Emerson, Joanne B.
Summary: Recent discoveries of mcr and mcr ‐like genes in genomes from diverse archaeal lineages suggest that methane metabolism is an ancient pathway with a complicated evolutionary history. One conventional view is that methanogenesis is an ancestral metabolism of the class Thermoplasmata . Through comparative genomic analysis of 12 Thermoplasmata metagenome‐assembled genomes (MAGs) basal to the Methanomassiliicoccales, we show that these microorganisms do not encode the genes required for methanogenesis. Further analysis of 770 Ca . Thermoplasmatota genomes/MAGs found no evidence of mcrA homologues outside of the Methanomassiliicoccales . Together, these results suggest that methanogenesis was laterally acquired by an ancestor of the Methanomassiliicoccales . The 12 analysed MAGs include representatives from four orders basal to the Methanomassiliicoccales, including a high‐quality MAG that likely represents a new order, Ca . Lunaplasma lacustris ord. nov. sp. nov. These MAGs are predicted to use diverse energy conservation pathways, including heterotrophy, sulfur and hydrogen metabolism, denitrification, and fermentation. Two lineages are widespread among anoxic, sedimentary environments, whereas Ca . Lunaplasma lacustris has thus far only been detected in alpine caves and subarctic lake sediments. These findings advance our understanding of the metabolic potential, ecology, and global distribution of the Thermoplasmata and provide insight into the evolutionary history of methanogenesis within the Ca . Thermoplasmatota.